Information for authors - Pacheco Romero, José (2016)
The Peruvian Journal of Gynecology and Obstetrics is the official publication of the Peruvian Society of Obstetrics and Gynecology. It aims to spread awareness of the specialty of obstetrics and gynecology and human reproduction among its members, professionals and workers related specialties in the area of sexual and reproductive health.